Vocational Teacher Learning Strategies during The Covid-19 Pandemic in SMK Muhammadiyah 1 Temon - Wijayanto, Asnawi; Mahmudah, Fitri Nur (Universitas Negeri Padang, 2022)
The implementation of learning carried out by vocational school teachers during the Covid-19 pandemic has a complexity of problems. This study aims to determine the extent to which the strategies of SMK teachers in carrying out the learning process during the Covid-19 pandemic. The method used in this research is qualitative with a case study approach. Data collection techniques with interview and documentation methods. Data analysis was carried out with the help of Atlas.ti software version 8. The results of this study include 1) before carrying out learning the teacher implements a lesson plan by preparing a syllabus and learning implementation tools; 2) using various kinds of media used in carrying out learning, namely using videos and modules; 3) using technology that supports learning activities by utilizing the google classroom and whatsapp group applications; and 4) using student learning evaluation to determine the extent to which students master the material that has been given.